2011
DOI: 10.5694/j.1326-5377.2011.tb03058.x
|View full text |Cite
|
Sign up to set email alerts
|

Doctors disciplined for professional misconduct in Australia and New Zealand, 2000–2009

Abstract: Objectives: To describe professional discipline cases in Australia and New Zealand in which doctors were found guilty of professional misconduct, and to develop a typology for describing the misconduct. Design and setting: A retrospective analysis of disciplinary cases adjudicated in five jurisdictions (New South Wales, Victoria, Queensland, Western Australia and New Zealand) in 2000–2009. Main outcome measures: Characteristics of the cases (setting, misconduct type, patient outcomes, disciplinary measure impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 9 publications
3
50
0
3
Order By: Relevance
“…These include patient volume, type of practice, history of disciplinary actions and, for doctors, performance issues during training and the country of their primary medical degree. Previous studies have identified associations between these factors and disciplinary outcomes [10, 12, 15, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…These include patient volume, type of practice, history of disciplinary actions and, for doctors, performance issues during training and the country of their primary medical degree. Previous studies have identified associations between these factors and disciplinary outcomes [10, 12, 15, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…The data available did not provide the reasons or the category for why a sanction had been imposed, but a more detailed evaluation of the reasons for referral to the GMC may go towards explaining the sex difference observed. In their research, Alam et al 4 and Elkin et al ,10 demonstrated not only that male doctors were more likely to be subject to disciplinary action, but also that the main offence for which a doctor was being disciplined was sexual misconduct. It is possible that male doctors are more likely to commit an offence involving sexual misconduct than their female colleagues, which may go towards explaining the sex difference seen in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of these studies have been performed in the USA,6 – 9 Canada,4 Australia and New Zealand,10 where the medical and legal systems differ from those of the UK, and therefore we felt that their findings may not be applicable to the UK population of doctors. These studies’ main objective was not necessarily to explore the association between doctors’ sex and disciplinary action.…”
Section: Discussionmentioning
confidence: 99%
“…Regulators have responded in various ways. Of disciplinary cases where doctors have been sanctioned by tribunals, 25% involve inappropriate prescribing, mainly drugs of dependency . In the USA, the Centers for Disease Control and Prevention is currently establishing prescribing norms to identify and intervene in cases of patients or providers who fall outside these norms .…”
Section: Introductionmentioning
confidence: 99%